Strategy for Continuous Quality Improvement at Vocational High School - Widodo, Cahyo; Isnantyo, Fajar Danur; Budianto, Aris; Sukatiman, Sukatiman; Wahyudi, Muhamad Nur Azmi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study analyzes the implementation of the Sistem Penjaminan Mutu Internal (SPMI) as a strategy for continuous quality improvement at Tambakboyo Vocational High School. Using a qualitative case study approach, data were collected through in-depth interviews with key stakeholders, participatory observation, and document analysis. Interviews involved school principals, teachers, administrative staff, students, and industry partners to gain insights into SPMI implementation. Observations were conducted through direct engagement in school activities, quality assurance meetings, and industry collaboration programs, while document analysis reviewed policies, reports, curriculum guidelines, and employment data. Data were analyzed using a qualitative descriptive approach through data reduction, display, and conclusion drawing, with triangulation ensuring validity. The findings highlight how stakeholders collaborate to align educational quality policies with industry demands through the PPEPP model (Penetapan, Pelaksanaan, Evaluasi, Pengendalian, Peningkatan Standard). Implementing SPMI positively impacts academic and non-academic quality, enhances graduate employability, and strengthens school-industry partnerships. A well-structured organization and consistent quality policies facilitate optimal outcomes, with industry collaboration ensuring curriculum relevance and skill alignment with labor market needs. This strategy enhances graduate competitiveness and serves as a model for addressing global educational and workforce challenges